Geriatric Rehabilitation Inpatients Roam at Home! A Matched Cohort Study of Objectively Measured Physical Activity and Sedentary Behavior in Home-Based and Hospital-Based Settings - Ramsey, Keenan A. (Elsevier Inc., 2022)
10.1016/j.jamda.2021.04.018